Pengaruh Future Time Perspective Terhadap Kematangan Karir Pada Mahasiswa - Aully Grashinta; Adinda Putri Istiqomah; Endro Puspo Wiroko (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2018)
One reason of the high unemployment is the lack of career planning. The individu needs career maturity and views about the future (future time perspective) so that she/he can choose the right job. This research aimed to determine the influence of future time perspective toward career maturity in college student. This study used a quantitative approach. Sample in this study are 156 of college students in Jabodetabek.The measurement tools is Carstensen and Lang Future Time Perspective scale (CL-FTP) and Career Maturity Inventory form C (IMC form C). The result shos that future time perspective affecting positively to career maturity in college student significantly (R2= 0.139; p = 0.000). Simple linear regression analysis stated that future time perspective contributed 13,9% to the career maturity and 86,1% influenced by other factors.